ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA - Ummul Huda; Edwin Musdi; Nola Nari (Ta'dib, 2019)
This research is motivated by the low mathematical representation ability of students in solving mathematical problem solving questions based on TIMSS data and facts in the field. The study aims to analyze the mathematical representation ability of MTsN Batusangkar students visually, verbally and symbolically in solving mathematical problem solving problems. This field research uses descriptive method. The instrument used is a description question and interview guide. Quantitative data based on test results were analyzed to determine the predicate of mathematical representation ability, while Miles and Huberman model wwas used to analyze qualitative data from interviews. The results show that students' mathematical visual and symbolic abilities are satisfactory, while verbal mathematical representations are less satisfactory.